The Integration of Environmental Education and Sustainable Development in Nursing and Health Technician Training: An Analysis of Curricular Descriptions - Essadki Samia; Lamsyah Rajae; Wahoud Fatima; Hajjaji Wissam; Boughoufa Radia; Elouadi Yassir; Zarouali Abdelbacit; Elmsellem Hicham (E3S Web of Conferences)
Environmental education and sustainable development are increasingly recognized as key concepts by various stakeholders, aiming to integrate them into training curricula from pre-school to university levels. However, no analysis has been conducted to assess how these dimensions are incorporated into the training curricula of Moroccan nurses and health technicians. The aim of the present study is to analyse 16 undergraduate training descriptions for nursing and health technology students at the Higher Institute of Nursing Professions and Techniques Health in Oujda (HINPTHO), accredited by the Moroccan Ministry of Higher Education. To this purpose, a criteria-based analysis grid was developed. Our results demonstrate that all the descriptors include competencies in waste management. A significant association was found between the degree of integration of environmental education and sustainable development concepts and the program option (p,0.005). In conclusion, it would be beneficial to introduce modules on eco-friendly practices and the use of renewable resources in future versions of these curricula. Overall, this research represents a pioneering effort in this area.